PENGARUH IDOL K-POP SEBAGAI BRAND AMBASSADOR, IKLAN, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK OLEH GENERASI Z PADA MARKETPLACE TOKOPEDIA - Ni Made Adrina Vionita Putri; Ni Putu Yeni Astiti; Ni Made Indah Mentari (Fakultas Ekonomi Universitas Warmadewa, 2025)
Tokopedia, as one of the largest marketplaces in Indonesia, is the main choice for generation z in fulfilling their shopping needs through online platforms. Generation z, known as digital consumers, is highly influenced by various factors in their purchasing decisions, including the influence of advertisements and celebrity figures. A rapidly growing phenomenon is the use of k-pop idols as brand ambassadors in product advertisements. The use of k-pop idols is not only intended to increase product popularity, but is also expected to form a strong brand image, which ultimately influences consumer purchasing decisions. This study aims to determine and analyze the influence of k-pop idols as brand ambassadors, advertisements and brand image on product purchasing decisions by generation z on the Tokopedia marketplace. The research population is generation z consumers domiciled in the city of Denpasar. The sample in this study was 112 respondents who were determined based on the purposive sampling method and using data analysis techniques, namely multiple linear regression analysis. The results of the study showed that brand ambassadors did not influence product purchasing decisions by generation z on the Tokopedia marketplace, while advertisements and brand image had a positive and significant effect on product purchasing decisions by generation z on the Tokopedia marketplace. Suggestions for further research include expanding the scope of the research by involving respondents from various generational groups, and conducting it over a longer period of time in order to provide a more in-depth picture of the factors that influence purchasing decisions in a broader context.